Trilhas ecológicas virtuais : uma metodologia para o ensino do Cerrado - (:unkn) unknown (Universidade Estadual de Goiás, 2021)
The Ecological Trails have been serving for a long time for ecotourism and Environmental Education actions through the country; the virtualization of these trails comes to the teacher's Aid for Science teaching. The general objective of the work is to verify how virtual Ecological Trails can be used as an interactive methodology to solve some of the difficulties encountered in teaching about the Cerrado biome to Elementary School II students, once the need for preserving the biome. The study was carried out through qualitative research and action research, analyzing questionnaires applied to students and teachers in two stages, at a partner school in the municipality of Goianésia-GO. To obtain the data, the application of electronic questionnaire was chosen. Students reported basic knowledge about the Cerrado, 4% pointed that they did not know that the Cerrado was the predominant biome in the state of Goiás in the first stage, varying to 100% in the second stage after applying the virtual trail. The professors reported how they taught their classes about the biome, what materials they used, what methods and quantity of presentations. The data obtained suggests that the Science classes are taught in a traditional way, using basically the textbook, without exploring all contents the worked, in addition, the students showed the superficiality of the information about the Cerrado in the first stage, demonstrating that the application of the virtual trail helped in the learning process by deepening this immediate knowledge shown in the first questionnaire.
Virtual ecological trails : a methodology for teaching the Cerrado
Keywords: Trilhas ecológicas virtuais; Educação ambiental; Bioma Cerrado; Virtual ecological trails; Environmental education; Cerrado Biome; CIENCIAS HUMANAS::EDUCACAO; OUTROS::CIENCIAS